Nutrient Status of the Leaves of Piliostigma Thonningii (Schum.) Milne-Redhead in the Guinea Savanna Zone of Nigeria - Mbaekwe, E. I.; Isichei, A. O. (2014)
The value of Piliostigma Thonningii as a browse plant in the Guinea Savanna Zone of Nigeria was assessed by analysing its leaves for nitrogen, phosphorus, potassium and carbohydrate contents. Sampling of the leaves was done from five different plots, at two different growth periods, that is March/April and October/November, representing the beginning of flush and the peak of vegetative growth respectively, and on both the apex and base of the twigs. Higher values for % total nitrogen, extractable potassium and % soluble sugar and starch were obtained at the beginning of flush when the leaves were younger than at the end when they were much older, indicating a decline of these essential nutrient elements with the age of the leaves. This trend was found to be statistically significant. The % total phosphorus was low, probably reflecting the reported low values for this essential element in Savanna soils. The nitrogen content compares very well with those of other species in the Savanna and is even higher than those of grasses at equivalent sampling period (October - November), indicating the importance of the leaves of P. thonningii as a source of browse for both wildlife and livestock at a critical period in the Guinea Savanna.